Investigating the Prevalence of Autonomic Neuropathy in Diabetic Patients with Urinary Irritation Symptoms Without a Known Cause - Ansari Djafari, Anahita; Javanmard, Babak; Koohifard, Ali; Hojjati, Fatemeh; Alinejad Khorram, Amir; Razzaghi, Zahra; Hojjati, Seyyed Ali (Urology Journal, 2024)
Purpose: Evaluating pseudomotor performance can be a valuable tool for investigating the peripheral autonomic nervous system in diabetic patients. Sudoscan, a simple and non-invasive method for assessing pseudomotor performance, has been developed in recent years. This study aimed to investigate autonomic neuropathy using Sudoscan in diabetic patients with lower urinary tract symptoms (LUTS) of unknown cause. Materials and Methods: In this cross-sectional study conducted from April 2022 to April 2023, we included 195 patients with type 2 diabetes who were referred to the urology clinic. We extracted demographic, clinical, and laboratory data from the patient files and evaluated urinary symptoms using the International Prostate Symptom Score (IPSS) questionnaire. Patients underwent Sudoscan testing to evaluate autonomic neuropathy in the physical medicine and rehabilitation clinic. To further assess urinary irritative symptoms, patients underwent urodynamic studies (UDS) and ultrasonography. Results: The Sudoscan test results showed that autonomic neuropathy was present in 77 patients (40%), with 43 (22.1%) having moderate and 44 (22.6%) having severe neuropathy. Patients with autonomic neuropathy were found to be older, had longer diabetes durations, higher average blood glucose levels, and higher creatinine levels. Additionally, we found a significant correlation between autonomic neuropathy and signs of high post-void residue on ultrasound and detrusor contraction disorders on UDS (p-value < 0.05). Conclusion: Our study found a higher prevalence of autonomic neuropathy in diabetic patients with LUTS using Sudoscan (40%). Longer diabetes duration and poor glycemic control were associated with an increased risk of autonomic neuropathy linked with LUTS, such as urge incontinence.